2020
DOI: 10.1021/acsanm.0c00551
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer MoS2 Transferred on Arbitrary Substrates for Potential Use in Flexible Electronics

Abstract: Molybdenum disulfide (MoS2), having unique optical and electrical properties, is a promising material for both nanoscale and flexible electronics. Direct growth of MoS2 over various substrates is possible by using several synthesis routes. But there is a pressing need for clean and damage-free transfer of MoS2 from the growth substrate onto other substrates for structural characterizations and novel device fabrication. In this work, we report about an efficient and clean route that can be applied for the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…Therefore, the efficacy of various growth promoters/catalysis was investigated to minimize growth temperature and maximize area coverage. The addition of synergistic additives such as fluorides, alkali metal halides, ,, and KOH and seed catalysis to the growth substrates lead to exponential growth area coverage. , Singh et al performed low-temperature NaCl-assisted growth of 1L-MoS 2 on amorphous, crystalline, and layered substrates and observed that NaCl forms the layer of Na 2 S and/or Na 2 SO 4 underneath the MoS 2 layer, which makes the layer-transfer process very smooth . Salt-assisted MoS 2 has shown high crystallinity, large mobility (∼100 cm 2 /V s), and high optical properties matching with the level of conventional CVD MoS 2 monolayers .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the efficacy of various growth promoters/catalysis was investigated to minimize growth temperature and maximize area coverage. The addition of synergistic additives such as fluorides, alkali metal halides, ,, and KOH and seed catalysis to the growth substrates lead to exponential growth area coverage. , Singh et al performed low-temperature NaCl-assisted growth of 1L-MoS 2 on amorphous, crystalline, and layered substrates and observed that NaCl forms the layer of Na 2 S and/or Na 2 SO 4 underneath the MoS 2 layer, which makes the layer-transfer process very smooth . Salt-assisted MoS 2 has shown high crystallinity, large mobility (∼100 cm 2 /V s), and high optical properties matching with the level of conventional CVD MoS 2 monolayers .…”
Section: Introductionmentioning
confidence: 99%
“…The water-soluble layer was completely dissolved during the transfer, reducing the unintended electron doping in WS 2. 26 This is the reason for that the intensity of the X exciton dominates the intensity of the X – trion in the PL spectrum of transferred WS 2 . Raman and PL spectra confirm that 1L WS 2 retains its optical properties after the transfer.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] By transferring the monolayer flakes on the transparent and flexible substrates, 1L‐MoS 2 can expand its utility to the flexible optoelectronic devices such as flexible field‐effect transistors (FETs), piezoelectric nanogenerators, organic light‐emitting diode displays, foldable displays, and memory devices. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 11 ] The transfer process of 1L‐MoS 2 is also exploited in multiple applications. [ 8 ] First, the transfer process is used in transferring the as‐grown films from the insulating substrates (like sapphire) onto the dielectric substrates (like SiO 2 ) for fabricating the complementary metal‐oxide‐semiconductor (CMOS) devices. [ 12 ] In addition, the transfer process is also extended to the transmission electron microscopy (TEM) sample preparation, [ 13 ] and the fabrication of vertical 2D heterostructures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation